2000
DOI: 10.1073/pnas.230451497
|View full text |Cite
|
Sign up to set email alerts
|

Rubisco activase constrains the photosynthetic potential of leaves at high temperature and CO 2

Abstract: Net photosynthesis (Pn) is inhibited by moderate heat stress. To elucidate the mechanism of inhibition, we examined the effects of temperature on gas exchange and ribulose 1,5-bisphosphate carboxylase͞oxygenase (Rubisco) activation in cotton and tobacco leaves and compared the responses to those of the isolated enzymes. Depending on the CO 2 concentration, Pn decreased when temperatures exceeded 35-40°C. This response was inconsistent with the response predicted from the properties of fully activated Rubisco. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
445
1
7

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 615 publications
(485 citation statements)
references
References 36 publications
25
445
1
7
Order By: Relevance
“…Previously, elevated temperatures were shown to negatively affect photosynthesis (Feller et al, 1998;Law and Crafts-Brandner, 1999;Haldimann and Feller, 2004), influencing leaf metabolism primarily through Rubisco activase properties and Rubisco activation state (Feller et al, 1998;Crafts-Brandner and Salvucci, 2000;Feller, 2004, 2005). It was also demonstrated that plants increase stomatal conductance under high temperatures (Salvucci and Crafts-Brandner, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, elevated temperatures were shown to negatively affect photosynthesis (Feller et al, 1998;Law and Crafts-Brandner, 1999;Haldimann and Feller, 2004), influencing leaf metabolism primarily through Rubisco activase properties and Rubisco activation state (Feller et al, 1998;Crafts-Brandner and Salvucci, 2000;Feller, 2004, 2005). It was also demonstrated that plants increase stomatal conductance under high temperatures (Salvucci and Crafts-Brandner, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the Rubisco activation activity, Rubisco activase has ATPase activity, and the ATPase activity is inhibited by ADP (Robinson and Portis, 1989b). The ATP/ADP ratio generally decreases under a higher CO 2 condition by an increase in ATP consumption (Gardestrom and Wigge, 1988), and this could down-regulate the activation state of Rubisco under elevated CO 2 conditions (Crafts-Brandner and Salvucci, 2000). Rubisco as well as Rubisco activase levels are considered to become excessive for photosynthesis under high CO 2 condition.…”
Section: Discussionmentioning
confidence: 99%
“…Rubisco activase is also involved in inhibition of photosynthesis by heat stress. Depending on plant species, the heat stress induces denaturation of Rubisco activase (Crafts-Brandner and Salvucci, 2000;Salvucci et al, 2001), association of Rubisco activase with the thylakoid membrane (Rokka et al, 2001), and appearance of new Rubisco activase isoform (Sánchez et al, 1995;Law et al, 2001), and these result in decreased photosynthetic rates.…”
mentioning
confidence: 99%
“…Cotton Activase-Procedures for the purification and assay of cotton Rubisco and the ␤-form of recombinant cotton activase have been described in detail previously (28,31,32). Point mutations were introduced into the cotton activase cDNA using the Gene Tailor kit according to the manufacturer's instructions (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%